2011
DOI: 10.5121/ijitcs.2011.1401
|View full text |Cite
|
Sign up to set email alerts
|

Anonymity And Verifiability In Multiattribute Reverse Auction

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The comparisons of the computation time of these protocols are shown in Figures , , and . Because did not provide strong privacy and public verifiability, the computation time of is much less than and the proposal. Because the proposal adopts hash function in place of public key, the computation time of proposal is much less than in the opening phase and the winner determination phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparisons of the computation time of these protocols are shown in Figures , , and . Because did not provide strong privacy and public verifiability, the computation time of is much less than and the proposal. Because the proposal adopts hash function in place of public key, the computation time of proposal is much less than in the opening phase and the winner determination phase.…”
Section: Methodsmentioning
confidence: 99%
“…Because did not provide strong privacy and public verifiability, the computation time of is much less than and the proposal. Because the proposal adopts hash function in place of public key, the computation time of proposal is much less than in the opening phase and the winner determination phase. According to Figures , , and , it is observed that the proposals computation time is reasonable and less than .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last two decades, auction mechanisms are studied and analyzed in different literatures . In spite of satisfying various security requirements, for example, privacy , anonymity , correctness, and verifiability , coercing and bid‐rigging are two serious attacks on sealed‐bid auction. Coercer is an adversary who is powerful enough to inflict the other bidders to bid low prices so that she could win the auction by bidding unreasonably low bid.…”
Section: Introductionmentioning
confidence: 99%